The Needs Analysis in Developing Case Method Model to Improve Students Translation Achievement in Translation in Language Teaching Subject - Masitorwarni Siregar (Randwick International of Education and Linguistics Science Journal, 2023)
The aim of this study is finding the Needs of the English Education students in studying the Translation in Language Teaching Subject at Universitas Negeri Medan. Qualitative research method using case study was utilized to depict a phenomenon on students' needs in learning Translation in Language Teaching Subject involving 60 English Education Students. The data was gathered through the use of questionnaires and interviews. Data were analyzed using the need analysis approaches by Hutchinson and Waters (1987) ; (1) wants (2) lacks, and (3) needs. The findings of the study revealed the students wants collaborative, cooperative, creative, communicative and problems solving activitis. They also stated their lack of knowledge and skills in translation vocabulary, in strategies of translation and translating subject areas. They need practice in translating words, idioms, collocation, cultural term and various genre.These need analysis results will be utilized for developing case method model of teaching in Trsnslation in English Langauge Teaching Subject